The Activities of War Archives Committee in Collecting Documents about the Victims of Totalitarian Regimes - Pięta, Jan (Genocidas ir rezistencija, 1997)
On 29 June 1992, the Military Archives’ Commission was set up to investigate Soviet repression on Polish territory. The Russian archives were primarily concerned with researching and copying documents relating to the presence of Polish prisoners of war and internees in the Soviet Union in 1939–1949, and to the crimes committed against other groups of society. The collection became the basis for scientific research and pedagogical work. The documents collected have already been used in numerous publications and historical research papers. They are also used by Polish university lecturers and staff of historical research institutions.
Keywords: Poland; repressions; Soviet Union; totalitarism